Exploring Mechanical Waves Through a Physics-Based Exploration Game for Secondary Education - Budi, Agus Setyo; Permana, Handjoko; Yasti, Arfa Hanania; Fitriani, Wulandari; Sari, Ni Larasati Kartika; Mutoharoh, Mutoharoh; Sabrina, Putri Marsha; Muliyati, Dewi (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2025)
Mechanical waves are an important part of high school physics, but they can be hard to understand because they are so abstract. The goal of this study was to create and test a physics-based digital exploration game that would help people understand wave phenomena. The game content included electromagnetic and mechanical waves, transverse and longitudinal waves, and the Doppler effect. This study employs a simplified instructional design model focusing on three key steps: analysis, design, and development. This model aims to enhance student engagement through the use of digital platforms and interactive learning resources such as educational games and mobile applications. Playzone was built on the CORE APPS platform. It had a shooting game set in a lab with tasks that required players to unlock objects, find clues, and get to areas that boost health. The expert reviewed the curriculum alignment, how the materials were presented, and how the evaluations worked. The assessment gave this game prototype a score of 89.33%, which means it is very feasible as learning media. These results show that the game could be very useful in the classroom because it makes learning about abstract physics concepts more fun and easier to understand by using stories and interactive activities.